KONSEPSI ALQURAN TENTANG MANUSIA - Santoso Irfan (State Institute of Islamic Studies (IAIN) Palu, 2007)
This article deals with the conception of the Qur’an on human beings. One of the major themes of the Qur’an is concerned with human beings and their functions on the earth. The Qur’an speaks of human beings in various terms such as al-insan, al-basyar, -‘abd and khalifah. The term Al-insan refers to the quality of thought and consciousness of human beings’; al-basyar signs their natural dimensions such as eating, drinking and dying; ‘abd indicates their obedience and piety, and khalifah denotes their freedom and creativity.Kata Kunci : Alquran, manusia, al-insan, al-basyar, ‘abd, khalifah